ANALISIS PROYEK PEMBANGUNAN LABORATORIUM SENTRAL UNIVERSITAS ANDALAS DENGAN METODE CRITICAL PATH METHOD - Auzan, Zulfakar; Desfita, Mediana; Nanda, Nanda; Sari, Kharisma Permata (Program Studi Teknik Sipil, 2024)
CPM (Critical Path Method) is a method for determining the priority of activities that must receive careful supervision attention so that activities can be completed according to plan. The problem in this study is that there are several jobs that are delayed and must be accelerated. The purpose of this study is to find out the activities that are on the critical path and compare the initial time and cost of the project with the time and cost after using the CPM method. This research method uses a quantitative approach. The results of the discussion in this study indicate that the critical path obtained in the Andalas University Central Laboratory Development Project is in work with the code B - D - E - H - J - L - M - O - Q - R. After getting the work that is on the critical path, the acceleration time calculation is carried out by adding 1 hour of overtime, resulting in an additional cost of Rp 15,894,743, this causes a change in the value of the project cost which was initially Rp. 55,924,829,000 to Rp 55,940,723,743.